Using Commercial Microwave Links to Improve Weather Forecasting and Emergency Response to Rainstorms - Yamauchi, Futoshi; Liu, Yanyan; Warner, James; David, Noam (2022)
Futoshi Yamauchi, Yanyan Liu, James Warner and Noam David The 8th Tokyo International Conference on African Development (TICAD8) Side Event: How Japan’s know-how can help address Africa’s food and nutrition challenges: Interventions and impacts SEP 28, 2022 - 6:00 TO 7:30PM JST